18.05: Second‐order effects of cantilever concrete filled double skin tube (CFDST) transmission towers. (13th September 2017) - Alhalaby, Mahmoud; Wang, Yong
ABSTRACT: Concrete Filled Double Skin Tubes (CFSDT) are an alternative to steel lattice transmission towers for supporting overhead transmission lines due to their many advantages including small footprint, fast construction, easy maintenance and elimination of large number of connections. CFDST transmission towers are tapered cantilever structure consisting of a CFDST pole and steel cross‐arms. Due to high slenderness, one key issue for static design of CFDST poles is the effect of second‐order bending (P‐Delta effect). A parametric study was conducted to investigate the second‐order effects exhibited by the CFDST transmission towers. The main parameters investigated include Horizontal to Vertical Load Ratio (HVLR) which reflects the range of environmental loads such as wind and ice, taper ratio (ratio of the bottom to the top outer diameter of the tower), and Hollow Section Ratio (HSR, ratio of the outer diameter of the inner steel tube to the inner diameter of the outer steel tube). The results of the numerical simulations indicate that the second‐order bending moments at failure of CFDST transmission towers are significant, magnifying the total bending moment by 20% or more of the first‐order bending moments. Based on the results of a parametric numerical investigation of second‐order effects of CFDST transmission tower under different conditions, this paper proposes a simplified analytical equation to estimate the second‐order bending moment.